Prevalence and clinical significance of cellular and acellular mucin in patients with locally advanced mucinous rectal cancer who underwent preoperative chemoradiotherapy followed by radical surgery. (January 2016) - Kang, C. M.; Lim, S.‐B.; Hong, S.‐M.; Yu, C. S.; Hong, Y. S.; Kim, T. W.; Park, J.‐H.; Kim, J. H.; Kim, J. C.
Abstract: Aim: The frequent presence of acellular mucin in specimens showing pathological complete response to preoperative chemoradiotherapy (CRT) and the poor response to preoperative CRT in mucinous rectal cancer have been reported. However, the prevalence and prognostic significance of cellular and acellular mucin have not been evaluated in resected specimens from patients with mucinous rectal cancer who undergo preoperative CRT. Method: We retrospectively evaluated the clinicopathological features and prognostic significance of mucin in resected specimens from 59 consecutive patients with mucinous rectal cancer who underwent long‐course CRT followed by resection between January 2000 and December 2009. Patients were categorized according to the presence of mucin, as identified by pathological analysis. The clinicopathological findings and oncological results were compared. Results: Mucin was identified in 25 of 59 patients with mucinous rectal cancer (42.4%). Mucin was more frequent in men (hazard ratio = 23.94, 95% confidence interval = 1.875–305.504, P  =   0.015) and in specimens showing a good tumour response grade (hazard ratio = 64.26, 95% confidence interval = 6.940–595.045, P  <   0.001). With a median follow‐up of 67.7 (range 8.6–133.2) months, the 5‐year overall survival (60.7% without mucin vs 51.4% with mucin, P  =   0.898) and disease‐free survival (59.9% without mucin vs 56.9% with mucin, P  =   0.813) did not differ between the groups. Conclusion: The presence of mucin in rectal cancer with mucinous differentiation after preoperative CRT and resection is associated with male gender and a good tumour response grade, without significant impact on oncological outcome.